Comparison of Manual Fetal Stimulation vs. No Fetal Stimulation on Non-Reassuring CTG during Intrapartum Fetal Surveillance - Fatima, Arwa; Yazdani, Tehreem; Chohan, Shazia Firdos; Anwar, Rabiah; Toheed, Mafia; Khan, Taimur Azam (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectiveness of manual fetal stimulation versus no fetal stimulation in managing non-reassuring Cardiotocography during intrapartum fetal surveillance.Study Design: Quasi-experimantal studyPlace and Duration of Study: Department of Obstetrics & Gynaecology, Pak Emirates Military Hospital, Rawalpindi Pakistan from Jan 2023 to Mar 2024.Methodology: In this study, n=242 patients were allocated randomly to either the manual fetal stimulation and Cardiotocography group or the no fetal stimulation and Cardiotocography group. The Inclusion criteria were women with singleton pregnancy at a gestation length of 37 weeks or more with non-reassuring Cardiotocography findings. The main parameters studied were the fetal heart accelerations, mode of delivery, Apgar score at the fifth minute, cord blood lactate level and admission to the neonatal intensive care unit.Results: Significantly higher number of patients (94.22%) showed fetal heart acceleration in the manual fetal stimulation group as compared to the no fetal stimulation group (80.17%). In the manual fetal stimulation group, 31.40% of the women underwent caesarean delivery compared to 37.19% in the no fetal stimulation group; however, the difference was not significant. Apgar score at 5th minute, cord blood lactate level and number of babies admitted to neonatal intensive care unit was also not different between the groups (p>0.05).Conclusion: Significantly higher number of cases having non-reassuring Cardiotocography showed the acceleration in fetal heart rate in response to manual fetal stimulation as compared to those not given this treatment. However, maternal and fetal outcomes were not different between the treatments.